A comparison of five different algorithms for EEG signal analysis in artifacts rejection for monitoring depth of anesthesia. (March 2016) - Liu, Quan; Chen, Yi-Feng; Fan, Shou-Zen; Abbod, Maysam F.; Shieh, Jiann-Shing
Highlights: Five different algorithms are compared for depth of anesthesia monitoring. Four kind of common artifacts in EEG are modeled as simulation data. Permutation entropy is more reliable in artifacts rejection and EEG bandwidth. Permutation entropy can track the drug effect more correctly. The combined index via ANN are better than single index. Abstract: Electroencephalography (EEG) signals have been commonly used for assessing the level of anesthesia during surgery. However, the collected EEG signals are usually corrupted with artifacts which can seriously reduce the accuracy of the depth of anesthesia (DOA) monitors. In this paper, the main purpose is to compare five different EEG based anesthesia indices, namely median frequency (MF), 95% spectral edge frequency (SEF), approximate entropy (ApEn), sample entropy (SampEn) and permutation entropy (PeEn), for their artifacts rejection ability in order to measure the DOA accurately. The current analysis is based on synthesized EEG corrupted with four different types of artificial artifacts and real data collected from patients undergoing general anesthesia during surgery. The experimental results demonstrate that all indices could discriminate awake from anesthesia state ( p  < 0.05), however PeEn is superior to other indices. Furthermore, a combined index is obtained by applying these five indices as inputs to train, validate and test a feed-forward back-propagation artificial neural network (ANN) model with bispectral index (BIS) as target. The combined index via ANN offers more advantages with higher correlation of 0.80 ± 0.01 for real time DOA monitoring in comparison with single indices.